PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KEPRIBADIAN SISWA DI MADRASAH ALIYAH NEGERI 1 KOTA MALANG - Lathifiyyah Haris; Muhammad Hanif; Nur Hasan (VICRATINA, 2019)
The purpose of this study is to describe the personality condition and to describe the importance of the role of Islamic religious education teachers in Malang 1 State Islamic Senior High School. The study was conducted with a type of qualitative research. The procedure of data collection is done by using the observation method, interview method by using the question and answer way verbally with research sources, and the documentation method that is in the form of notes, transcripts, and so on. In this study, the condition of student personality is said to be good can be seen from how students order in carrying out activities in the madrasa, polite and polite attitude to good speech. And based on what is done by a teacher of Islamic religious education in shaping the personality of students by giving examples and good example, providing student motivation, interacting and maintaining communication with students, and using subtle language. It can be concluded that the personality possessed by students in Madrasah Aliyah Negeri 1 in Malang city is good and the teacher of Islamic religious education in shaping students' personalities in accordance with the existing theories in the thesis.Keywords: Role, Personality